The Internet and the language classroom - Dudeney, Gavin, 1964-; Cambridge University Press (Cambridge ; New York : Cambridge University Press, 2007)
This text explores the theory and application of the Internet in the traditional classroom environment; from using the Web and e-mail to creating Web projects and running e-mail exchanges.
Guidelines Activities Tools for online work Teacher development Websites.
Includes bibliographical references (pages 165) and index.
Keywords: Language and languages -- Study and teaching -- Computer network resources; Internet in education